2007
DOI: 10.1002/elsc.200620174
|View full text |Cite
|
Sign up to set email alerts
|

Oral Bioaccessibility and Leaching: Tests for Soil Risk Assessment

Abstract: A set of test methods for estimating the risk for human health (oral bioaccessibility tests) and groundwater (leaching tests) was applied to contaminated soils from three sites with different sources of contamination. The bioaccessible soil concentrations of the contaminants cadmium, lead, nickel, benzo(a)pyrene and dibenz(a,h)anthracene were considerably lower than the total concentrations. The leached concentrations of the polycyclic aromatic hydrocarbons, cadmium and nickel were below the EU drinking water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…The key contaminants included in this work are arsenic (As), lead (Pb) and cadmium (Cd) as they are potentially harmful to human health (ATSDR, 2007b;ATSDR, 2007a;ATSDR, 2008) and the most common elements undergoing bioaccessibility research Ruby et al, 1993;Ruby et al, 1996;Albores et al, 2000;Oomen et al, 2002;Marschner et al, 2006;Chan et al, 2007;Datta et al, 2007;Drexler and Brattin, 2007;Finzgar et al, 2007;Hansen et al, 2007;Juhasz et al, 2007aJuhasz et al, , 2007bLjung et al, 2007;Sarkar et al, 2007;Subacz et al, 2007;Turner and Ip, 2007;Van de Wiele et al, 2007;Beak et al, 2008;Moseley et al, 2008;Girouard and Zagury, 2009;Morman et al, 2009;Nagar et al, 2009;Poggio et al, 2009;Smith et al, 2009;Zhang et al, 2009;Demetriades et al, 2010;Juhasz et al2010). …”
Section: Introductionmentioning
confidence: 99%
“…The key contaminants included in this work are arsenic (As), lead (Pb) and cadmium (Cd) as they are potentially harmful to human health (ATSDR, 2007b;ATSDR, 2007a;ATSDR, 2008) and the most common elements undergoing bioaccessibility research Ruby et al, 1993;Ruby et al, 1996;Albores et al, 2000;Oomen et al, 2002;Marschner et al, 2006;Chan et al, 2007;Datta et al, 2007;Drexler and Brattin, 2007;Finzgar et al, 2007;Hansen et al, 2007;Juhasz et al, 2007aJuhasz et al, , 2007bLjung et al, 2007;Sarkar et al, 2007;Subacz et al, 2007;Turner and Ip, 2007;Van de Wiele et al, 2007;Beak et al, 2008;Moseley et al, 2008;Girouard and Zagury, 2009;Morman et al, 2009;Nagar et al, 2009;Poggio et al, 2009;Smith et al, 2009;Zhang et al, 2009;Demetriades et al, 2010;Juhasz et al2010). …”
Section: Introductionmentioning
confidence: 99%
“…In general, human contact or oral ingestion of soils is described as occasional (Body et al 1999;Pouschat and Zagury 2006;Lemly 2007;Morman et al 2009) and in some cases intentional (Smith et al 2000). Several studies have reported the potential risk caused by oral ingestion of metalpolluted soils (Hansen et al 2007;Denys et al 2008;US EPA 2009). The potential risk of ingestion of metal contaminants is currently assessed through bioaccessibility approaches, understanding bioaccessibility as the fraction representing the availability of metal absorption when dissolved in surrogates of body fluids or juices after oral exposure.…”
Section: Introductionmentioning
confidence: 98%
“…The potential risk of ingestion of metal contaminants is currently assessed through bioaccessibility approaches, understanding bioaccessibility as the fraction representing the availability of metal absorption when dissolved in surrogates of body fluids or juices after oral exposure. In this regard, several in vitro tests that simulate gastrointestinal conditions have been proposed to estimate the bioaccessibility of some elements from ingested soils (Carrizales et al 2006;Intawongse and Dean 2006;Ljung et al 2007;Hansen et al 2007;Makris et al 2008;Bosso and Enzweiler 2008;Madrid et al 2008;Smith et al 2009;Zagury et al 2009;Morman et al 2009). To date, Se has not been addressed.…”
Section: Introductionmentioning
confidence: 98%
“…Grøn et al (2007) and Hansen et al (2007) estimated maximum bioaccessibility (25-40 %) at lowest "humic content" (2 %) and lower bioaccessibility (6-24 %) at 4-5 % "humic content." However, simply scaling PAH bioaccessibility to SOC content cannot explain the variations in bioaccessibility data from reported soil samples (Table 1).…”
Section: Introductionmentioning
confidence: 99%